Upaya Meningkatkan Hasil Belajar Gerak Ritmik dengan Metode Jigsaw Kelas IV SDN 1 Pelimbangan - A. Saripudin (South Sulawesi Education Development, 2024)
This research aims to improve the learning outcomes of Basic Rhythmic Movement students using the Jigsaw method in class IV at SDN 1 Pelimbangan. This type of research is Classroom Action Research, this research emerged based on the problems faced by the researchers themselves. This research consists of 4 stages, namely planning, action, observation and reflection. The data collection techniques used are observation, knowledge tests, work tests, attitude tests and documentation. The results of this research show that using the Jigsaw method can improve learning outcomes in learning basic rhythmic movements and can be confident in basic rhythmic movements in cycle I. effective, but learning was more effective in cycle two even though there were still some students who did not achieve completeness in learning basic rhythmic movements. Keywords:,